Pengaruh Bauran Pemasaran Dan Citra Merek Terhadap Keputusan Pembelian Yang Berdampak Pada Kepuasan Konsumen (Studi Kasus pada Konsumen Produk Merek Eiger). - Hakim, Alvin Nuril; Wahono, Budi; Basalamah, Muhammad Ridwan (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Consumer behavior is the behavior that consumers display in searching for, purchasing, using, evaluating, and disposing of products and services that they hope will satisfy their needs. The aim of this research is to analyze the influence of the marketing mix and brand image on purchasing decisions which have an impact on consumer satisfaction. The sample was 100 consumers who bought Eiger brand products at the Eiger Pare-Kediri Outlet. The sampling technique is purposive sampling, namely a technique for sampling data sources with certain considerations. The sample consideration in this research is consumers who have purchased Eiger brand products at the Eiger Pare-Kediri Outlet more than once. The test equipment in this research uses multiple linear regression. The results of the analysis can be concluded that: (1) the marketing mix has a positive effect on purchasing decisions. (2) Brand image has a positive effect on purchasing decisions. (3) Purchasing decisions have a positive effect on consumer satisfaction. Keywords: marketing mix, brand image, purchasing decisions and consumer satisfaction